Providing a Nursing Care Plan as a Requirement for Secondary Prevention for People Living With HTLV-1 - Aben-Athar, Cintia Yolette Urbano Pauxis; Sampaio, Edilson Coelho; Pinto, Denise Silva; Vallinoto, Antonio Carlos Rosário; Cayres Vallinoto, Izaura Maria Vieira (Frontiers in Medicine, 2022)
The absence of nursing care plans aimed at people living with HTLV-1 (PLHTLV) led us to develop and test a proposed nursing care plan based on the evaluation of 55 PLHTLV to outline interventions according to the clinical stage. Methods: After interviews with symptomatic patients, nursing diagnoses were made using the NANDA International Nursing Diagnoses (The International Nursing Knowledge Association). Subsequently, interventions were selected through the Classification of Nursing Interventions (NIC), and expected results were selected through the Classification of Nursing Outcomes (NOC). Results: The actual diagnoses included (ii) chronic pain, (iii) impaired urinary elimination, and (iv) sexual dysfunction; the health promotion diagnosis was (i) risk-prone health behavior; and the risk diagnoses were (i) risk of feeling powerless and (ii) risk of falls in adults. Nursing care must prevent the lack of adherence to monitoring, establish goals and promote family involvement. A safe home environment requires intervention for fall prevention. Full support in understanding pharmacological and nonpharmacological therapies for chronic pain is needed. Interventions allow patients with impaired urinary function to be reintroduced to society. For sexual dysfunction, it is necessary to discuss safe sex and behavioral changes. Regarding risk behaviors, it is necessary to guide the patient/family, adapt language to the education level of these individuals, and help them better accept the condition, among other guidelines. Conclusion: The development of a nursing care plan for PLHTLV is essential for preventing the rapid progression of disease and the improvement of the quality of life of PLHTLV and should be included in the multidisciplinary approach to the secondary level of prevention of HTLV-1.